2017
DOI: 10.1371/journal.pone.0179994
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical carotid atherosclerosis and sCD163 among virally suppressed HIV patients in Botswana compared with uninfected controls

Abstract: ObjectivesHuman immune deficiency virus (HIV) is associated with increased cardiovascular disease (CVD) risk, yet the relationship between HIV and carotid atherosclerosis / monocyte activation among virally suppressed HIV-infected patients in sub-Saharan Africa is not well understood.MethodsWe measured traditional CVD risk factors, bilateral distal common carotid intima media thickness (cIMT), presence of carotid plaque and plasma sCD163 levels among virally suppressed HIV-infected adults and HIV-uninfected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
2
19
1
Order By: Relevance
“…Fourteen studies were conducted from Europe, 20,2226,30,31,34,35,39,41–43 followed by America (4 studies), 10,27,28,38 Asia (4 studies), 11,21,29,32 and Africa (4 studies). 33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th. 20,29,33,39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies were conducted from Europe, 20,2226,30,31,34,35,39,41–43 followed by America (4 studies), 10,27,28,38 Asia (4 studies), 11,21,29,32 and Africa (4 studies). 33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th. 20,29,33,39…”
Section: Resultsmentioning
confidence: 99%
“…33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th. 20,29,33,39…”
Section: Resultsmentioning
confidence: 99%
“…Results presented in the current analysis are in line with those from other, smaller, studies conducted in SSA. Gleason et al [49], Fourie et al [46] and Mosepele et al [18] all compared HIV-positive to HIV-negative participants in Ethiopia, South Africa and Botswana respectively, and observed no increase in CIMT based on HIV or ART status. Fourie et al [46], even found a lower CCA-IMT for the HIV-positive compared to the HIV-negative group.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution made by ART to the development of CVD is a matter of debate. Although ART restores immune function, inflammatory markers do not return to normal levels, indicating ongoing low-grade inflammation, which is associated with CVD risk [1618]. Older ART regimens evidently carry a high risk of metabolic side-effects, including lipodystrophy, altered glucose metabolism and dyslipidaemia, and have been associated with increased carotid intima-media thickness (CIMT), a marker of subclinical atherosclerosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte activation is associated with extensive pro-inflammatory biomarker expression (particularly IL-6, hsCRP, cystatin C) with consequent inflammatory endothelial damage that in turn allows circulating low-density lipoprotein (LDL) cholesterol particles entry into the intima where they become oxidized (oxLDL) [18**]. Monocyte activation, accompanied by elevated monocyte-specific markers (e.g., sCD14, sCD163, MCP-1), also promotes monocyte migration into the intima of large arteries where, in the presence of large amounts of oxLDL, they become dysfunctional foam cells [19].…”
Section: Introductionmentioning
confidence: 99%